The Bed of Procrustes: Philosophical and Practical Aphorisms (Incerto #3) - Nassim Nicholas Taleb (Italy Penguin Books, 2010)
A condensed guide to life, Nassim Nicholas Taleb's The Bed of Procrustes is an invaluable collection of aphorisms to help you navigate the modern world. Why are we so often unwilling to accept that life is unpredictable? In this brilliant book Nassim Nicholas Taleb distils his idiosyncratic wisdom to demolish our illusions, contrasting the classical values of courage, elegance and erudition against modern philistinism and phoniness. Only by accepting what we don't know, he shows, can we see the world as it really is.
Keywords: Nonfiction; Philosophy